«Behind It A River Flashing Blue» ( From Anna Akhmatova's Verse) - BARKLAY, IRINA (Bulletin of Yerevan University H: Russian Philology, 2021)
The article examines the literary links between Anna Akhmatova and William Shakespeare and explores Christian symbols prevalent in Akhmatova»s verse Reading Hamlet. Her inclusion of Shakespearean language and Christian symbols reveal the wide use of the colors white, black and red. In contrast, Akhmatova demonstrates the poetic role of the light-blue color, which became her nomina sacra.
Keywords: literary connections, Shakespeare, Akhmatova, Andersen, Grey, Theuriet, the light-blue color, nomina sacra